TINJAUAN PENINGKATANAN PROGRAM STUDI DIPLOMA TIGA MENJADI SARJANA TERAPAN TERHADAP TECHNICAL AND VOCATIONAL EDUCATION TRAINING (TVET) - Syaflan Sandi Harta Putra; Nizwardi Jalinus; Ambyar Ambyar; Nurhasan Syah; Refdinal Refdinal (Ensiklopedia of Journal, 2022)
The purpose of writing this article is to examine the philosophy of TVET in the era of the industrial revolution 4.0 to increase the Diploma Three (D-III) study program to an Applied Bachelor (D4) in improving the quality of vocational education in Indonesia. The TVET learning strategy was developed taking into account the right targets, competency objectives and performance indicators, as well as a measurable transformation of the achievement of TVET's vision and mission of the XXI Century. The role of TVET is to prepare a generation that is ready to face the industrial world in the 4.0 revolution. TVET is designed as learning to increase real impact for students. In line with this, the Directorate General of Vocational Education program with the improvement of the Diploma Three Study Program (D-III) to an Applied Bachelor (D4) is very helpful in accelerating the vision and mission of TVET itself. The improvement of this vocational study program aims to create competent, skilled graduate human resources in accordance with the needs of the business world and the industrial world (DUDI). This program is also welcomed by the organizers of vocational education because vocational education is getting brighter and can compete in skilled human resources.